Bjerkandera carnegieae comb. nov. ( Phanerochaetaceae , Polyporales ) a wood-decay polypore of cactus - Gerardo Robledo; Karen K. Nakasone; Beatriz Ortiz-Santana (Plant and Fungal Systematics, 2021)
Poria carnegieae was described from Arizona growing on the woody ribs of the saguaro cactus, Carnegiea gigantea , and was transferred to Ceriporiopsis due to morphological evidence. Posterior phylogenetic studies showed a relationship of Poria carnegieae with Bjerkandera . New sequence data and morphologic evidence are presented to support the transfer of Ceriporiopsis carnegieae to Bjerkandera .